Построение инвестиционного портфеля Г. Марковица для украинского фондового рынка - Чепорова, Г.Е.; Ногас, И.Л. (Культура народов Причерноморья, 2013)
В статье рассмотрена экономико-математическая модель формирования оптимального портфеля Г. Марковица; осуществлена практическая реализация модели в пакете MS Excel с использованием статистических данных о котировках акций на украинских фондовых биржах. Построен оптимальный портфель ценных бумаг с использованием акций известных украинских предприятий; определены состав, доходность и риск оптимального портфеля на украинском фондовом рынке. Применение теории портфеля Г. Марковица позволяет сформировать оптимальный портфель. В статті розглянута економіко-математична модель формування оптимального портфеля Р. Марковіца; здійснена практична реалізація моделі в пакеті MS Excel з використанням статистичних даних про котировки акцій на українських фондових біржах. Побудований оптимальний портфель цінних паперів з використанням акцій відомих українських підприємств; визначені склад, доходність та ризик оптимального портфеля на українському фондовому ринку. Застосування теорії портфеля Г. Марковіца дозволяє сформувати оптимальний портфель. The article considers the economic and mathematical model of the G.Markowits optimal portfolio; performed practical implementation of the model in the MS Excel package using statistical data on the share price on the Ukrainian stock exchanges. There’s built an optimal portfolio of securities with shares of famous Ukrainian enterprises; defined composition, return and risk on the optimal portfolio of the Ukrainian stock market. The most difficult procedure in the implementation of the Markowitz model is computing needed to assess how the various courses of the shares or debentures of change with respect to rates of other stocks or bonds. Markowitz model does not account for transaction costs. Application of G.Markowits portfolio theory allows you to create the optimal portfolio consisting of shares in enterprises of different industries and banking. This portfolio has a lower risk than any portfolio consisting entirely of shares of one company from consideration. This allows to get the desired level of profitability. Considered model works quite effectively in conditions of developed and stable countries. In conditions of instability is also advisable to use Sharp's model, which takes into account the fluctuation of individual stocks relative fluctuations of the stock market.